Correlación de corte de agua adimensional para pozos horizontales basada en Kuo&Desbrisay (2012)
The numerical simulation was used to determine the sensitivity of the behavior of water coning at various reservoir parameters in horizontal wells. The simulation results were then used to develop a correlation simplified the prediction of water coning for horizontal Wells previously developed by the authors Kuo & DesBrisay in his “Simple method for prediction of water coning” but evaluated in vertical wells originally. The correlation is generally as sensitivity studies covering a wide range of parameters reservoir ratio of vertical to horizontal permeability, called anisotropy ratio of 0,01 to 1; distance from horizontal drilling of oil-water contact called Db from 5,5 to 34,5 ft; production rate of 500 to 10.000 of gross liquid; mobility ratio 1,0 to 9,8.